Development of Picture Stories Electronic Book (E-Book) for German Learning at Class X Madrasah Aliyah Negeri 1 Malang City - Syamsiatur Rohma (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The purpose of this research and development is to develop learning media in the form of e-books with pictorial stories. This research and development uses a research model developed by Borg and Gall and has been modified by researchers. The stages of developing Borg and Gall that have been modified by researchers are: 1) research and data collection, 2) planning and development of product drafts, 3) expert validation, 4) revision of expert validation results, 5) field trials and 6) product revisions end. The data obtained in this study are quantitative data and qualitative data. Both data were obtained from filling out expert validation questionnaires and filling out observation sheets by two observers in field trial activities. Subjects in this study, namely students of class X MAN 1 Malang City who are taking odd semesters. From the results of the validation of the media experts that have been carried out, the product eligibility results are 80%, while the results of the material expert validation get 80% of the product eligibility results. Based on the validity level criteria, it can be concluded that the picture story e-book product is included in the level of "very valid" or suitable for use in learning. Meanwhile, the results of filling out observation sheets and student response questionnaires by observers in field trial activities showed that the media developed was interesting and could help students practice reading skills in German.